Anti-inflammatory effect of polyphenols from Chilean currants (Ribes magellanicum and R. punctatum) after in vitro gastrointestinal digestion on Caco-2 cells: Anti-inflammatory activity of in vitro digested Chilean currants. (August 2019) - Burgos-Edwards, Alberto; Martín-Pérez, Laura; Jiménez-Aspee, Felipe; Theoduloz, Cristina; Schmeda-Hirschmann, Guillermo; Larrosa, Mar
Graphical abstract: Highlights: The effect of in vitro gastrointestinal digestion (GID) on Ribes fruits was studied. The in vitro anti-inflammatory effect of resulting polyphenols after GID was assessed. The digested extracts reduced the IL-8, IL-6 and TNF-α levels in Caco-2 inflamed cells. The digested extracts decreased the COX-2 and iNOS gene expression in Caco-2 cells. The digested Ribes spp. extracts inhibited human COX-1 and COX-2 activity in vitro. Abstract: The polyphenol-enriched extracts (PEEs) of Chilean currants Ribes magellanicum and R. punctatum were submitted to in vitro gastro-intestinal digestion and their anti-inflammatory activities were assessed using differentiated human Caco-2 (clone C2BBe1) cells stimulated with interleukin 1β (IL-1 β). The inhibitory effect of non-digested and digested PEEs towards human cyclooxygenase 1 (COX-1) and COX-2, and the gene expression of COX-2 and inducible nitric oxide synthase (iNOS) was also evaluated. The digested PEE from R. punctatum decreased the secretion of IL-8, IL-6, and TNF-α; whereas R. magellanicum reduced IL-6 and TNF-α in the Caco-2 cells ( p < 0.05). Both digested extracts significantly down-regulated the mRNA expression of COX-2 and iNOS ( p < 0.05). PEEs showed 60% of inhibition towards COXs, with higher inhibition against COX-2. The PEEs from R. punctatum displayed better anti-inflammatory activity in all the experiments. Our results suggest that R. magellanicum and R. punctatum might be useful against intestine inflammatory conditions.